1997
DOI: 10.1080/0042098975510
|View full text |Cite
|
Sign up to set email alerts
|

Joint Choice of Tenure and Dwelling Type: A Multinomial Logit Analysis for the City of Chongju

Abstract: This paper explores the plausible variables that influence choices in the Chongju housing market. A joint model of tenure and dwelling type is estimated within the multinomial logit framework. The logit model of housing choice is fitted to the whole sample and to two sub-samples, which are categorised on the basis of neighbourhood quality. The empirical results do not exhibit a uniform pattern over the three sample cases. In the case of the whole sample, housing choice is influenced by the age, educational lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…Histogram of three tenure by planned length of time to own house 12Cho (1997) analyzed four tenure choices.…”
mentioning
confidence: 99%
“…Histogram of three tenure by planned length of time to own house 12Cho (1997) analyzed four tenure choices.…”
mentioning
confidence: 99%
“…Most of these studies relied on the workhorse of MNL models when it comes to estimating the joint choice of tenure and dwelling type/ location, without careful consideration of the error structure as to whether assumptions on the distribution of error terms were satisfied. Examples were Cho (1997) and Skaburskis (1999) who both investigated the joint choice of dwelling and tenure type. Although the rationale for the use of a genuine NL model was explicitly recognised by Cho and Skaburskis, they used MNL models due to the limitation of employed software and estimation technique at the time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies have focused on two dimensions of housing choice, with the most common being tenure choice (Cho, 1997;Rapaport, 1997;Skaburskis, 1999;Tu and Goldfinch, 1996). Most of these studies relied on the workhorse of MNL models when it comes to estimating the joint choice of tenure and dwelling type/ location, without careful consideration of the error structure as to whether assumptions on the distribution of error terms were satisfied.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(1) In general, dwelling type and size are strongly associated with demographic attributes. Studies on housing demand found that the aged, householders who are professionals, and households with school-age children are not inclined to choose rented apartment housing 34) and that an increase in household size, age, or income is associated with demand for larger dwellings. 35) However, this trend is not uniform across the city.…”
Section: Methodsmentioning
confidence: 99%